From Linnaeus to 2024—a history of Thysanoptera taxonomic diversity studies - Mound, Laurence A. (Zootaxa, 2024)
The number of recognized Thysanoptera genera and species worldwide increased from one and four in 1758, to 36 and 135 in 1900, and almost 790 and 6500 in 2024. In this essay the work of the authors who have been particularly significant in this growth of knowledge about thrips diversity is discussed, decade by decade.